Blended learning to enhance English writing assignments without using online tools - Parichart Charernwiwatthanasri (Universitas Islam Malang, 2021)
From face-to-face to online teaching an English for Reading and Writing course is challenging to provide learning strategies and assessments that fit the pedagogical style of the online environment since there are many online tools (e.g. translation machine, grammar check software, and websites) for assistance in English writing. This study aims to investigate students' learning strategies in taking an online writing assignment, with an emphasis on using authentic assessments to encourage students to avoid using online tools and plagiarism in their writing. The findings show that during online learning, students made use of online tools, and they searched for the information on the internet as an assistance in writing an assignment. However, using Blended Learning and four different types of writing tasks significantly reduces the use of online tools, and it enhances students' active participation in the assessment process. The guided instructions of each task also help students to improve their writing skills, and most of the students preferred to work in small groups to complete the activities online which enhanced interaction and the sense of an online learning community.